Clinical and Laboratory Predictors of Poor Outcomes in Pediatric Cerebral Malaria in Nigeria - Olayinka Rasheed Ibrahim; Amudalat Issa; Rafiu Taofeek Babatunde; Michael Abel Alao (Oman Medical Journal)
Objectives: Cerebral malaria remains poorly understood despite being a common manifestation of severe malaria in children, often associated with poor outcomes. We sought to describe the burden of childhood cerebral malaria and identify factors predictive of poor hospitalization outcomes (death and neurological outcomes) and short-term neurological sequelae. Methods: We conducted a retrospective review of children diagnosed with cerebral malaria at a tertiary hospital in northwestern Nigeria from 1 January 2019 to 31 December 2022. We retrieved relevant information, including hospitalization outcomes (discharge, death, and neurological sequelae) and neurological status at follow-up. Results: Of 8295 pediatric admissions, 948 cases were severe malaria; from those, 284 cases of cerebral malaria were identified, representing a prevalence of 3.4% and 30.0%, respectively. Clinical and laboratory features were comparable between survivors and non-survivors, except hypoxemia (p =0.016), duration of loss of consciousness (p< 0.001), acidosis (p =0.002), white blood cell count (p =0.006), serum sodium (p =0.005), and serum creatinine (p < 0.001). Hypoxemia (adjusted odds ratio (AOR) = 6.071; 95% CI: 1.672–22.043), serum creatine > 1.5 mg/dL (AOR = 6.720; 95% CI: 2.160–20.905), and the first 24 hours of hospitalization (AOR = 5.934; 95% CI: 2.423–14.535) were predictors of hospitalization death. Forty-nine (19.6%) of 250 survivors had neurological complications at discharge. Age under five years increased the odds of neurological complications at discharge (OR = 2.059; 95% CI: 1.094–3.876). At follow-up, 24 (49.0%) of the 49 patients with neurological complications recovered fully. Conclusions: This study demonstrates that cerebral malaria is associated with a high mortality rate and significant neurological complications, particularly in children under five years old. Hypoxemia and elevated serum creatinine levels were associated with an increased risk of in-hospital death.